Analysis of Goals Scored in European Football Championship with Offensive Parameters of Semi Final Teams 2020/2021 - Zivanovic, Vladimir (Sport - nauka i praksa, 2025)
The study aims to analyze the characteristics of the goals scored in a sample of 51 games and offensive parameters of teams that reached the semi-finals in a tournament held in 2020/ 2021. The analysis of the data used descriptive statistics i.e., the chi-square test and cross tabulation. The results showed statistically significant difference i.e., data that more goals were scored in the second half (83) than in the first (52), x2=7.119, p
Keywords: goals; performance indicators in football; tournament competition; video analysis